Question-answer sequences in conciliation hearings and interviews with political candidates - Cortes Gago, Paulo; Bittencourt Silveira, Sonia (Sociolinguistic Studies, 2007)
This paper works at the intersection between applied linguistics and ethnomethodological conversation analysis. Applied linguistics has as its central concern the interest in the study of discourse, especially in the professions, and addresses itself to real world problems of language use in interaction. In conversation analysis, social action must be interpreted taking centrally into account participant’s conduct in sequences of action in interaction. Combining the two, social meaning is studied from an inherently emic point of view. In this paper we will compare the interactional practice of asking questions in conciliation hearings in consumers’ relations and in interviews with political candidates. The following questions have guided our study: 1) What actions are associated with the practice of questioning and answering in these settings? 2) What do they tell us about the institutional mandate of its participants? Results show that the point of convergence in the two data sets is the conduciveness embedded in the mediator’s and the interviewer’s questions. Differences are tied to their specific institutional mandates of framing legally the situation and trying to bring disputants to an agreement in the first case, and clarify the public opinion with confrontational questions in the second case, considering the candidates’ future government programs and, when this is the case, their previous political career.